Synthesis and characterization of Ti(IV), Zr(IV) and Al(III) salen-based complexes - Hipolito, Joana; Alves, Luis; Martins, Ana (European Journal of Chemistry, 2021)
New Ti(IV), Zr(IV) and Al(III) salen-based complexes of formulae [(L)TiCl2], 2, [(L)ZrCl2], 3, and [(L)Al(CH2CH(CH3)2)22], 4, where L = meso-(R,S)-diphenylethylene-salen, were synthesized in high yields. [(L)Al(CH2CH(CH3)2)22] is a bimetallic complex that results from the reaction of H2L with either 1 or 2 equivalent of Al(CH2CH(CH3)2)3. The solid-state molecular structures of compounds 2 and 4·(C7H8) were obtained by single-crystal X-ray diffraction. Crystal data for C44H54Cl2N2O2Ti, (2a): monoclinic, space group C2/c (no. 15), a = 27.384(1) Å, b = 12.1436(8) Å, c = 28.773(2) Å, β = 112.644(2)°, V = 8830.6(9) Å3, Z = 8, μ(MoKα) = 0.350 mm-1, Dcalc = 1.146 g/cm3, 26647 reflections measured (5.204° ≤ 2Θ ≤ 50.7°), 8072 unique (Rint = 0.0967, Rsigma = 0.1241) which were used in all calculations. The final R1 was 0.0640 (I > 2σ(I)) and wR2 was 0.1907 (all data). Crystal data for C62H72Cl2N2O2Ti (2b): monoclinic, space group P21/c (no. 14), a = 19.606(1) Å, b = 12.793(1) Å, c = 23.189(2) Å, β = 105.710(4)°, V = 5599.0(7) Å3, Z = 4, μ(MoKα) = 0.291 mm-1, Dcalc = 1.182 g/cm3, 37593 reflections measured (3.65° ≤ 2Θ ≤ 50.928°), 10304 unique (Rint = 0.0866, Rsigma = 0.1032) which were used in all calculations. The final R1 was 0.0593 (I > 2σ(I)) and wR2 was 0.1501 (all data). Crystal data for C67H97Al2N2O2 (4·(C7H8)): triclinic, space group P-1 (no. 2), a = 10.0619(9) Å, b = 16.612(2) Å, c = 21.308(2) Å, α = 67.193(5)°, β = 78.157(6)°, γ = 77.576(5)°, V = 3176.8(6) Å3, Z = 2, μ(MoKα) = 0.088 mm-1, Dcalc = 1.063 g/cm3, 42107 reflections measured (5.382° ≤ 2Θ ≤ 51.624°), 12111 unique (Rint = 0.0624, Rsigma = 0.0706) which were used in all calculations. The final R1 was 0.0568 (I > 2σ(I)) and wR2 was 0.1611 (all data). The solid-state molecular structure of [(L)Al(CH2CH(CH3)2)22] reveals that both metal centres display a slightly distorted tetrahedral geometry bridged by the salen ligand. Both [(L)TiCl2] and [(L)ZrCl2] complexes display octahedral geometry with trans-chlorido ligands.